2021
DOI: 10.1016/j.dld.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation as fuel for acute liver injury in COVID-19

Abstract: Background A cytokine storm conceivably contributes to manifestations of corona virus disease (COVID-19). Inflammatory cytokines such as interleukin-6 (IL-6) cause acute liver injury while serum detectability indicates systemic inflammation. Aims We explored a link between systemic IL-6, related acute phase proteins and liver injury in hospitalized COVID-19 patients. Methods 655 patients with suspected COVID-19 were screened in the emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 47 publications
2
62
2
Order By: Relevance
“…In a larger American cohort that included 5700 patients, 59% and 39% showed AST and ALT values above ULN, respectively [ 10 ]. In agreement with our data, two independent studies from Northern Italy [ 12 ] and Austria [ 15 ] demonstrated upregulation of AST in 44% and 42% of admitted patients with SARS-CoV-2, respectively. In contrast, fewer patients (only 16% and 20%) had abnormal AST levels in the studies from Zhejiang Province [ 4 ] and Rome [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a larger American cohort that included 5700 patients, 59% and 39% showed AST and ALT values above ULN, respectively [ 10 ]. In agreement with our data, two independent studies from Northern Italy [ 12 ] and Austria [ 15 ] demonstrated upregulation of AST in 44% and 42% of admitted patients with SARS-CoV-2, respectively. In contrast, fewer patients (only 16% and 20%) had abnormal AST levels in the studies from Zhejiang Province [ 4 ] and Rome [ 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, in the liver, the effect of COVID-19 has been evaluated in relatively few studies, which focused on alterations in liver histopathology and biochemistry during the course of infection in patients who succumbed to the virus [ 3 , 4 , 5 , 6 , 7 , 8 ]. Several up-to-date studies have attempted to evaluate parameters related to liver injury in American and Asian cohorts [ 3 , 8 , 9 , 10 , 11 ], as well as in European cohorts [ 12 , 13 , 14 , 15 ]. Yet liver disease in the context of SARS-CoV-2 infection remains largely unknown, thus minimizing the understanding of abnormal liver function in terms of the overall outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 69 ] concluded after studying 657 patients infected with SARS-CoV-2 in Wuhan that not only male sex, but also serum concentration of high sensitivity CRP ≥ 10 mg/L and a neutrophil-to-lymphocyte ratio ≥ 5 predispose to liver injury during the course of COVID-19, defined in this survey as a serum level of ALT or total bilirubin greater than the ULN. Thus, an inflammatory background may be closely related to liver function impairment as a complication of the disease[ 70 , 71 ]. Metabolic syndrome and isolated hepatic steatosis were also evaluated as potential risk factors for liver dysfunction during the course of SARS-CoV-2 infection.…”
Section: Metabolic Syndrome and Inflammation As Factors Predisposing mentioning
confidence: 99%
“…COVID-19 mainly leads to acute respiratory symptoms, including fever, dry cough, and dyspnea. Besides, 16-76% of COVID-19 patients manifest as varying degrees of abnormal liver biochemistry tests[ [2] , [3] , [4] ], which are secondary to viral infection of liver cells, liver hypoxia, drug-induced liver injury, and immune-inflammatory reaction[ 5 , 6 ]. Notably, a minority of them may progress into liver failure[ 7 ].…”
mentioning
confidence: 99%